ChemInform Abstract: Design and Synthesis of Carbohydrate Based Medium Sized Sulfur Containing Benzannulated Macrocycles: Applications of Sonogashira and Heck Coupling. Issue 46 (24th October 2013) - Hussain, Altaf; Yousuf, Syed Khalid; Sharma, Deepak K.; Rao, L. Mallikharjuna; Singh, Baldev; Mukherjee, Debaraj
Abstract The synthesis of 8‐, 9‐, 10‐, 11‐, and 13‐membered ring compounds having a carbohydrate ring fragment is established by intramolecular Sonogashira and Heck coupling reactions.